Prospects for the utilization of solid biomass and RDF in district heating - Rajczyk, Rafał (Instal, 2024)
The article discusses the possibilities of using three selected fuels in district heating. Solid biomass was represented by agro straw pellets and PKS (palm kernel shell), and an alternative fuel – RDF – was tested as well. The introduction deals with the use of biomass and alternative fuels for heat generation in general, and presents the market situation with particular emphasis on the amount of biomass currently used in Poland and international trade. For the imported fuel – PKS, transport processes and their impact on the achieved ecological effects were discussed. The following section presents the physical and chemical properties of the tested fuels and their ashes. The chemical composition, characteristic temperatures of the ash were presented, and selected operational indices were determined, the usefulness of which in predicting operational problems is referred to later. The fuels were combusted in fluidized bed technology, which, after grate technology, is the second most commonly used in district heating, and one of its most important advantages is fuel flexibility. Emission and operational tests were performed on a laboratory rig with a fluidized bed. The contents of individual components of exhaust gases were determined, and the agglomeration processes of the bed material and bottom ash were analyzed. The conducted research showed that both fuels based on solid biomass have favourable properties and are suitable for use in heating. In turn, when burning RDF, attention should be paid to the possibility of operational problems, primarily related to the significant chlorine content.
Keywords: combustion; solid biomass; fluidized bed; alternative fuels; district heating